Pseudo hypoaldosteronism type 1B due to novel deletion mutation in SCNN1A gene - Ahmad, Noman; Atiyah, Meshal; Al Ghamdi, Balgees Abdulhadi; Al Enizi, Halah Faleh; Al Zahrani, Ali Saeed (International Journal of Contemporary Pediatrics, 2019)
Pseudo hypoaldosteronism type 1B (PHA1B) is a systemic form of salt wasting. Children present after the first week of life with typical symptoms of an adrenal crisis. PHA1B is caused by autosomal recessive homozygous mutations in genes encoding epithelial sodium channels (ENaC) subunits α, β and γ. ENaC are widespread and present in renal tubules, airways, colon, sweat and salivary glands. Electrolyte imbalance is significant with severe hyponatremia, hyperkalemia and metabolic acidosis. In early life until approximately one year of age electrolytes remain unstable despite active management but then gradually improve. The mainstay of treatment is high dose salt replacement, sodium bicarbonate and sodium polystyrene therapy. The adequate treatment and monitoring can result in normal physical and psychomotor development. We present a case of PHA1B with severe intractable electrolyte imbalances in neonatal period. The genetic sequence revealed a novel homozygous deletion mutation in exon 4 of the SCNN1A gene (c.942delC, p.N315Tfs*16).